Pickleball for all : everything but the "kitchen" sink - Simon, Rachel (Writer) (Dey St., an imprint of William Morrow, 2022)
"Learn everything you need to know about America's fastest-growing sport, with stories and tips from the world's top pros, the weekend warriors, and the devoted ambassadors who make up the wonderful world of pickleball." -- Back cover.